Aromaticity‐Controlled Energy Storage Capacity of the Dihydroazulene‐Vinylheptafulvene Photochromic System. Issue 41 (23rd August 2016) - Skov, Anders B.; Broman, Søren Lindbæk; Gertsen, Anders S.; Elm, Jonas; Jevric, Martyn; Cacciarini, Martina; Kadziola, Anders; Mikkelsen, Kurt V.; Nielsen, Mogens Brøndsted
Abstract: Photochemical conversion of molecules into high‐energy isomers that, after a stimulus, return to the original isomer presents a closed‐cycle of light‐harvesting, energy storage, and release. One challenge is to achieve a sufficiently high energy storage capacity. Here, we present efforts to tune the dihydroazulene/vinylheptafulvene (DHA/VHF) couple through loss/gain of aromaticity. Two derivatives were prepared, one with aromatic stabilization of DHA and the second of VHF. The consequences for the switching properties were elucidated. For the first type, sigmatropic rearrangements of DHA occurred upon irradiation. Formation of a VHF complex could be induced by a Lewis acid, but addition of H2 O resulted in immediate regeneration of DHA. For the second type, the VHF was too stable to convert into DHA. Calculations support the results and provide new targets. We predict that by removing one of the two CN groups at C‐1 of the aromatic DHA, the heat storage capacity will be further increased, as will the life‐time of the VHF. Calculations also reveal that a CN group at the fulvene ring retards the back‐reaction, and we show synthetically that it can be introduced regioselectively. Abstract : Full of energy : An increase in the solar energy storage capacity of the dihydroazulene (DHA)–vinylheptafulvene (VHF) photo/thermoswitch is achieved by fusing a benzene ring to the DHA isomer (see figure). In contrast, the relative stability is interchanged by benzannulation of the VHF isomer.